Mitochondrial adaptations in aged skeletal muscle: effect of exercise training - Ziaaldini, M. M; Hosseini, S. Ra; Fathi, M (Physiological research, 2017)
The aging process is associated with a decline in mitochondrial functions. Mitochondria dysfunction is involved in initiation and progression of many health problems including neuromuscular, metabolic and cardiovascular diseases. It is well known that endurance exercise improves mitochondrial function, especially in the elderly. However, recent studies have demonstrated that resistance training lead also to substantial increases in mitochondrial function in skeletal muscle. A comprehensive understanding of the cellular mechanisms involved in the skeletal muscle mitochondrial adaptations to exercise training in healthy elderly subjects, can help practitioners to design and prescribe more effective exercise trainings.
Keywords: fyziologická adaptace; fyzická vytrvalost; Physical Endurance; kosterní svaly; stárnutí; Exercise; Humans; Mitochondria, Muscle; lidé; cvičení; PPARGC1A; Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1-alpha; svalové mitochondrie; Aging; Muscle, Skeletal; Adaptation, Physiological